First report of Strawberry crinkle virus in Argentina - Perotto, Maria Cecilia (2014)
Strawberry crinkle virus (SCV) is one of the most frequent viruses affecting strawberry worldwide, and responsible for important reductions in yield and fruit quality. Stunted dwarfed plants with distorted leaves were found in Lules (26°55′22″S 65°20′15″W), Tucumán province, Argentina, in 2010, suggesting the virus presence. Total nucleic acids were isolated from leaves of 26 strawberry plants (Fragaria x ananassa cv. Camarosa) showing symptoms using the modified cetyltrimethylammonium bromide method (CTAB) as performed by Chang et al. (2007). Healthy strawberry plants previously tested by grafting to indicator plants (Fragaria virginiana clone UC-12, F. vesca clone UC-6 and cv. Alpine) were used as negative controls.